Fotogrammetria diretta con RPAS - Filiberto Chiabrando; Andrea Lingua; Marco Piras (GEOmedia, 2015)
Nowadays, the RPAS (Remotely Piloted Aircraft Systems) or UAV (Unmanned Aerial Vehicle) are often used, with onboard calibrated digital camera for photogrammetric purpose such as DTM and DSM, orthophotos and map realization etc., combining the digital images with a minimum sufficient number of ground control points using semiautomatic image-matching techniques combined with traditional bundle-block approach (Barazzetti et al, 2012;. Chiabrando et al, 2012; Haala et al, 2011;. Lingua et al 2008;. Remondino et al., 2011). In this case, the RPAS performances allows to obtain high quality product , considering the pixel size and the accuracy of the DTM/DSM which could be obtained with automatic procedures. This is a good condition for semi-automatic procedure using a bundle-block photogrammetric approach. But is it possible to realize a direct photogrammetry? And what are the limits? Several navigation sensors (GPS/GNSS e IMU-MEMS) are embedded onto RPAS in order to realize an autonomous flight. The quality of these sensors, in term of accuracy, depends on the model of RPAS and its purpose. The navigation solution (position and attitude) is estimated by the internal RPAS sensor and can be employed to directly georeferencing the images, in order to produce an easy and quick description and analysis of the overlooked area. In this paper, the authors describes an investigation over the limits of some commercial RPASs, defining a dedicated procedure to valuate their performance, especially considering the use of RPAS for direct photogrammetry. The first results encourage the use of RPAS for geomatic applications, because the cost and the quality of the obtained product are quite interesting.